The simultaneous determination of silicic, boric and carbonic acids in natural water via ion-exclusion chromatography with a charged aerosol detector - Otsuka, Yu; Nakatani, Nobutake; Takahashi, Takuya; Kozaki, Daisuke; Mori, Masanobu; Tanaka, Kazuhiko (MDPI, 2016)
The simple and simultaneous determination of silicic, boric and carbonic acids was made using ion-exclusion chromatography (IEC) and a Corona™ charged aerosol detector (C-CAD). Silicic and boric acids were separated by the column packed with a weakly acidic cation-exchange resin in H+-form and ultra-pure water eluent, and the detector responses were improved by the addition of acetonitrile to eluent. Under the optimized conditions, the simultaneous determination of weak inorganic acids, except for carbonic acid, was successfully performed. When the conversion column packed with a strong acidic cation-exchange resin in Na+- or K+-form was inserted between the separation column and the detector, weak inorganic acids including carbonic acid could be detected by the C-CAD. The calibration curves were linear in the range of 0.5–10 mg·L−1 as Si for silicic acid (r2 = 0.996), 10–100 mg·L−1 as B for boric acid (r2 = 0.998) and 1.3–21 mg·L−1 as C for carbonic acid (r2 = 0.993). The detection limits based on three times the standard deviation were 0.03 mg·L−1 as Si for silicic acid, 0.40 mg·L−1 as B for boric acid and 0.08 mg·L−1 as C for carbonic acid. This method was applicable to river, hot spring and drinking water.